Prevalence and characteristics of rmtB and qepA in Escherichia coli isolated from diseased animals in China - Deng, Yuting; Zeng, Zhenling; Tian, Wei; Yang, Tong; Liu, Jian-Hua (Frontiers in Microbiology, 2013)
16S rRNA methylase and QepA, a fluoroquinolone efflux pump, are new mechanisms of resistance against aminoglycosides and fluoroquinolone, respectively. One of 16S rRNA methylase genes, rmtB, was found to be associated with qepA, were both located on the same transposable element. In this study, we intended to determine the current prevalence and characteristics of the 16S rRNA methylase genes and qepA, and to study the association between rmtB and qepA. A total of 892 Escherichia coli isolates were collected from various diseased food-producing animals in China from 2004-2008 and screened by PCR for 16S rRNA methylase genes and qepA. About 12.6% (112/892) and 0.1% (1/892) of isolates that were highly resistant to amikacin were positive for rmtB and armA, respectively. The remaining five 16S rRNA methlyase genes were not detected. Thirty-six (4.0%) strains carried qepA. About 32.1% of rmtB-positive strains harbored qepA, which was not detected in rmtB-negative strains. Most strains were clonally unrelated, while identical PFGE profiles of rmtB-positive isolates were found in the same farm indicating clonal transmission. Conjugation experiments showed that rmtB was transfered to the recipients, and qepA also cotransfered with rmtB in some cases. The spread of E. coli of food animal origin harboring both rmtB and qepA suggests that surveillance for antimicrobial resistance of animal origin as well as the study of the mechanisms of resistance should be undertaken.